Hubungan Aktivitas Fisik dan Kualitas Tidur dengan Kejadian Hipertensi pada Masyarakat - Nurkhalis Yuspi Marbun; Alam Bakti Keloko; Tukiman T; Namora Lumungga Lubis (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aimed to determine the relationship between physical activity and sleep quality with the incidence of hypertension in the working area of Belawan Public Health Center in 2026. This was a quantitative study with a cross-sectional approach. The sample consisted of 96 respondents aged 30-49 years selected using an accidental sampling technique. Data were collected through structured interviews using the International Physical Activity Questionnaire (IPAQ) and Pittsburgh Sleep Quality Index (PSQI), and then analyzed using the chi-square test at a 95% confidence level. The results showed that the majority of respondents had high physical activity levels (67.7%), poor sleep quality (66.7%), and experienced hypertension (17.7%). Statistical analysis indicated that there was no significant relationship between physical activity and the incidence of hypertension (p-value = 0.151). Conversely, sleep quality had a significant relationship with the incidence of hypertension (p-value = 0.008). In conclusion, sleep quality was significantly associated with the incidence of hypertension, whereas physical activity was not associated.